RANCANGAN SISTEM INFORMASI DATA INVENTORY PADA RESTU CELULAR: PHP, mySQL, Information Systems - Suana, Irma (JURNAL AKADEMIKA, 2017)
At the National Land Agency District National Tebo is located in Tebo Regency is one of the government agencies that do not use the website as a medium of information when people want to get that information must come first in office, asking to side particular , the purpose of the research that the general public will be well informed full of BPN office Tebo anywhere via the internet. The system is built using PHP and MySQL with data input profiles, news, photos, information, announcements, and registration.